Population Dynamics and Milk Production Potential of Bovines in the Arid Region of Western Rajasthan - Singh, Surenda; Kalla, J C (Annals of Arid Zone, 2016)
The resource endowments of the arid regions are supposed to be more suitable for dairying enterprise. Under the existing state of technology, the population of milch animals is one of the important determinants of milk production in’ the arid region of -.ye5tefD ’Rajasthan. An attempt was made’ to quantify the temporal population n changes of the breedable bovine population and relate these spatially with the milk production of the region. Despite wide inter-district variations, the total and breedable cattle population over the last, ,27 years have, registered sizable ’positive annual rates of growth. 1:he districts marked by high aridity, viz. Jaisalmer, Bikaner, Barmer, Churu and Jodhpur had registered higher growth rates of breedable cattle populations. Higher growth rates of breedable buffalo pop,ulat ions on the other hand, were localised to certain districts .like Sikar, Jhunjhunu and Churu, which are’ endowed with better irrigation facilities. The districts with high concentrations of livestock population had high degrees of spatial association with milk ’production performance. The n(ed for development of fodder and infrastructural resources for realising greater mil production in the region has been stressed.